Theoretical substitution of the patterns of the influence of components from post-consumer wood on the physical and mechanical characteristics of combined blockboards - Lesiv , Lev (Forestry, Forest, Paper and Woodworking Industry, 2025)
The use of Post-consumer wood (PCW) in the production of blockboards is a relevant direction aimed at the rational use of secondary resources and reducing the shortage of primary wood. The article provides a theoretical justification of the patterns of influence of the constituent elements of PCW-made blockboards on their physical and mechanical characteristics. The main attention is paid to the analysis of the stress-strain state of the boards, dimensional stability and durability of structures taking into account the anisotropy of the material. An approach to predicting the characteristics of blockboards based on the finite element method (FEM) is proposed, which allows modeling the behavior of structures under conditions of variable humidity and temperature. It is established that orthogonal, cylindrical and transversal schemes can be used to describe the anisotropy of wood, the choice of which depends on the orientation of the fibers and the size of the rails. The feasibility of using a cylindrical coordinate system for analyzing the dimensional stability of boards in the processes of shrinkage and swelling is substantiated, especially when the curvature of the annual layers significantly affects the quality of the product. An applied method for calculating the physical and mechanical characteristics of PCW rails has been developed, taking into account anisotropy and changes in humidity and temperature conditions of the environment. The proposed mathematical models make it possible to predict the strength and dimensional stability of blockboards depending on the design parameters and operating conditions, as well as to optimize structures at the design stage. The optimal ratio of the cross-section of rails (1:3) and the recommended angle of inclination of annual layers (not less than 60°) have been established, which contributes to reducing the amount of rutting. For the first time, a mathematical dependence has been obtained that describes the influence of the width of PCW rails on the dimensional stability of the plates, which allows rational selection of structural parameters. The results of the study confirm that the use of FEM and new mathematical models increases the accuracy of predicting the properties of PCW-made blockboards, contributes to the development of new design solutions and ensures their strength, reliability and durability.